Wind and solar power: An overview of non-market externalities and metrics - Meireles, M.; Fátima Lima; Edimar Ramalho; Madaleno, M.; Marta Ferreira Dias; Alves, M. R. (ICOPEV 2024 – The 6th International Conference on Production Economics and Project Evaluation, 2024)
Wind and solar power projects are relevant alternatives to fossil fuels and constitute a focal point for achieving greenhouse gas (GHG) emissions reduction in national strategies (e.g. Portugal). Yet, despite the relevant contribution to electricity generation, renewable energy projects also entail externalities, i.e. impacts that inadvertently affect ecosystems and communities at different levels, and that are not accounted for by the agents that produce them. For instance, health benefits provided by avoided emissions of wind and solar power deployment as positive externalities, or biodiversity loss that affects flora and fauna as negative externalities. Valuation of externalities may resort to a myriad of methods, among which contingent valuation, travel cost valuation, or market price-based methods. This paper intends to summarize the main externalities ascribed to wind and solar power projects and the methods of their economic valuation. To promote a better understanding between impacts and possible valuation alternatives a specific research string was adopted and applied to the research database; followed by an exclusion/inclusion criteria that allowed to establish a restricted sample of articles to assess. This overview may contribute to discerning different types of economic valuation for each socioeconomic and environmental category, contributing to the economic and energy engineering scope. Finally, policy implications for energy transition based on wind and solar power projects are provided.